THE EFFECT OF WORK ENVIRONMENT AND JOB SATISFACTION ON PERFORMANCE OF EMPLOYEE MANAGERS IN GORONTALO DISTRICT - Rudin, Wati; Mozin, Sri Yulianty; Rizal (Journal of Economic, Business, and Administration (JEBA), 2024)
The purpose of this study was to determine and analyze (1) how the influence of the work environment on the performance of personnel managers in Gorontalo Regency, (2) how the influence of job satisfaction on the performance of personnel managers in Gorontalo Regency; (3) how the influence of the work environment and job satisfaction together on the performance of personnel managers in Gorontalo Regency. This study uses a quantitative approach to the type of survey research. The technique used to obtain data is a questionnaire technique (questionnaire) or a list of questions. Data analysis techniques were carried out through descriptive analysis, validity test, reliability test, analysis requirements test, multiple regression analysis, partial test (t test), F test, and R^2 test (coefficient of determination). The technique of collecting data is through a survey of 64 personnel managers in Gorontalo Regency. Data analysis was performed by multiple linear regression. The results of this study indicate that: (1) the work environment has a positive and significant effect on the performance of personnel managers in Gorontalo Regency. This means that the better the work environment, the higher the performance of personnel managers in Gorontalo Regency; (2) job satisfaction has a positive and significant effect on the performance of personnel managers in Gorontalo Regency. This means that the higher the job satisfaction felt by the personnel managers, the higher the performance of the personnel managers in Gorontalo Regency; (3) work environment and job satisfaction together have a positive and significant effect on the performance of personnel managers in Gorontalo Regency. The higher the work environment and job satisfaction, the higher the performance of personnel managers in Gorontalo Regency.